Tюркізми османської хроніки «Історія Наїми» як стилістично-інформаційний код - Кульчинський, О.Б. (Культура народов Причерноморья, 2013)
Стаття присвячена одній зі стилістичних особливостей османського літопису поч. 18 ст. «Історія Наїми». Проведений на основі корпусної методології лексикостатистичний аналіз хроніки засвідчив, що в порівнянні з іншими османськими творами в ній домінують тюркські дієслова та масдари. Втім, домінація не є такою відчутною, аби стверджувати, що автор радикально опонував літературним канонам. Вжиток тюркізмів пояснюється намаганнями автора вплинути на адресата тексту. Ключові слова: літопис, текст, стиль, тюркізми, османська проза. Статья посвящена одной из стилистических особенностей османской летописи нач. 18 в. «Истории Наимы». Проведенный на основании корпусной методологии лексико-статистический анализ хроники засвидетельствовал, что по сравнению с другими османскими произведениями в ней доминируют тюркские глаголы и масдары. Между тем, их доминирование не настолько ощутимо, чтобы утверждать, что автор радикально оппонировал литературным канонам. Употребление тюркизмов объясняется попытками автора повлиять на адресата текста. Ключевые слова: летопись, текст, стиль, тюркизмы, османская проза. The article is devoted to one of stylistical peculiarities of an 18 c. Ottoman chronicle “History of Naima”. This Ottoman prose work for a long time has been the subject of special interest for literary critics, historians and linguists due to its stylistic features. The comparison of the chronicle frequency lexical parameters with other Ottoman prose texts by corpus approach demonstrated that it had been created according to the canons of Ottoman Prose Literature and rules of its language norm. Yet at the same time, «History of Naima» differs from other texts in some obscure, inexpressive form, which let the annalist work stay quite famous in Ottoman Literature for two centuries and not be forgotten as was the chronicle “Seyahatname” of the famous traveler Evliya Chelebi. Verbs and masdars of Turkic origin prevail in Naima’s History in comparison with other Ottoman Prose. Meanwhile this prevailing is not so noticeable as to claim that the author radically opposed literary canons. More frequent using of Turkic words in the chronicle can be explained by author's attempts to influence the recipient of the text with the aim to convince him of some political ideas. Key words: chronickle, text, style, Turkic words, Ottoman prose.